Evaluation of human papillomavirus of high and low oncogenic risk in the oral cavity of HIV positive patients - Ávila, Maira (2020)
Objective. Perform human papilomavirus (HPV) detection and typing in the oral cavity in a group of HIV positive patients, treated at the Center for Care of Patients with Infectious Diseases (CAPEI) of the Faculty of Dentistry-Central University of Venezuela. Methods. Thirty-one oral swabs from HIV-positive patients were evaluated to detect HPV infection using the INNO-LiPA Reverse Hybridization System that detects 28 HPV genotypes of high and low oncogenic risk. Results. The 61.0% of the evaluated samples had an HPV infection. The low risk genotype 6 was the most frequent (73.68%), followed by genotypes 18, 11 and 16 with 63.16%, 37.0%, and 32.0%, respectively. Seventy-four percent of HPV positive samples had multiple infections, being the more frequent the mixed coinfection (35.70%), with HPV genotypes 6/18 of low and high oncogenic risk, 21.40% with genotypes 11/6/18 and 6/11, each one, followed by 14.30% of the samples presented infection with HPV-6/11/16/18 and 7.10% with the 11/16 genotypes of low and high oncogenic risk. Conclusions. The high frequency of infection with high oncogenic risk HPV types and the presence of multiple genotypes observed in the oral cavity of HIV positive patients, who did not present lesions compatible with this infection in the extra and intraoral examination, indicates that molecular diagnostic methods are important in the detection of subclinical and latent infections, which may allow better follow-up and more timely management of these patients with a higher risk of developing malignant lesions in the oral cavity.